Including highly educated migrants in academia to improve their health-protocol for a pilot intervention - Khadra Yasien Ahmed; Lars T. Fadnes; Lars T. Fadnes; Bernadette Kumar; Wegdan Hasha; Wegdan Hasha; Esperanza Diaz; Esperanza Diaz (Frontiers Media S.A., 2024)
IntroductionNorway's healthcare system needs a diversified work force to meet societal demands for improved cultural competence. However, many migrants in Norway who were educated as health professions in their home countries are not practicing these professions. This may negatively affect their physical and mental health and hinder their personal social integration. Though good health is often seen as a precondition for work, relevant working activities can also improve health. However, including health professionals with foreign education in academic institutions prior to receiving necessary accreditation is a complex task. This study will pilot an intervention aiming to improve health through meaningful integration of these professionals in academic environments.Materials and methodsThis paper is a protocol for a non-randomized pilot intervention study targeting migrants who are waiting for their health education accreditation in Norway. To test the benefits of meaningful activity on health and explore possibilities for implementing such activity, we have designed a six-month long intervention consisting of including nurses, doctors, and other highly educated migrants with healthcare backgrounds between 20 and 67 years of age, into health-related working tasks, at two higher education institutions in Bergen, Norway. The intervention will be tailored according to the participant's expertise. This hybrid type 2 pilot protocol paper will present how feasibility, fidelity, dose received (satisfaction), and dose of exposure (participation), will be assessed and whether the intervention is experienced as beneficial for the participants' health as primary outcome utilizing both quantitative and qualitative methods.ConclusionWe present a complex, personalized intervention that has the potential for large scale implementation in the future. By thoroughly presenting our designed intervention and assessment methods, this protocol will add to the study's transparency and facilitate replicability and comparison with future studies. This study will be of benefit to the migrants themselves, policy makers, government agencies and academia at large as it can point to a unique and sustainable way of speeding up the integration of highly educated migrants in their respective fields in a new host country.